The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1002/pon.3642
|View full text |Cite
|
Sign up to set email alerts
|

The influence of sense of control and cognitive functioning in older cancer patients' depression

Abstract: Older cancer patients' sense of control orientation over the course of illness and the cause of illness predicted the levels of depressive symptomatology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 38 publications
2
11
0
2
Order By: Relevance
“…For example, results for chance sleep locus of control indicate the importance of discussing personal sense of control over sleep and correcting the misconception that healthy sleep is out of one’s control. This is consistent with many behavioral medicine interventions that highlight the importance of sense of control in achieving better health (Mystakidou, Tsilika, Parpa, & Galanos, 2015; Nuccitelli et al, 2017). Further, there is very little knowledge regarding what components of CBT-I are best delivered in-person or via an Internet intervention.…”
Section: Discussionsupporting
confidence: 88%
“…For example, results for chance sleep locus of control indicate the importance of discussing personal sense of control over sleep and correcting the misconception that healthy sleep is out of one’s control. This is consistent with many behavioral medicine interventions that highlight the importance of sense of control in achieving better health (Mystakidou, Tsilika, Parpa, & Galanos, 2015; Nuccitelli et al, 2017). Further, there is very little knowledge regarding what components of CBT-I are best delivered in-person or via an Internet intervention.…”
Section: Discussionsupporting
confidence: 88%
“…Some have demonstrated that patients with high external LOC have poor coping skills and may experience increased rates of depression (14, 23, 27). Other studies have shown that an elevated external LOC can allow patients to better adapt to their illness because they are able to separate themselves from their illness and see it as being the responsibility of their physician (a powerful other) (12).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies suggest that high external LOC may be associated with decreased quality of life and mental well-being while others demonstrate improved outcomes (3, 1113) . Prior research in cancer patients suggest that a high external LOC may be related to increased rates of depression (14). The primary objective of our study was to evaluate the manner in which LOC impacts QOL and mental well-being of patients with advanced stage cancer who had been referred to a cancer center’s supportive care clinic.…”
Section: Introductionmentioning
confidence: 99%
“…The present study has some limitations. First, our subjects may have been lacking one or more factors that were previously shown to affect the association between depressive symptoms and age, including comorbidities, 19,29 poor cognitive function, 18,19,29,49e53 other somatic symptoms, 7,19,37 social factors, such as caring for young children, career or economic stresses, 54,55 social support factors, 7,29 locus of control, 56 and Charlson comorbidity scores. 29 We especially should have assessed cognitive function, which has been shown to be associated with depression 18,19,49,50 and is prevalent in cancer patients.…”
Section: Discussionmentioning
confidence: 99%